Double- and triple-crystal X-ray diffractometry of microdefects in silicon - Molodkin, V.B.; Olikhovskii, S.I.; Kyslovskyy, Ye.M.; Len, E.G.; Reshetnyk, O.V.; Vladimirova, T.P.; V.V. Lizunov, V.V.; Lizunova, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The generalized dynamical theory of X-ray scattering by real single crystals allows to self-consistently describe intensities of coherent and diffuse scattering measured by double- and triple-crystal diffractometers (DCD and TCD) from single crystals with defects in crystal bulk and with strained subsurface layers. Being based on this theory, we offer the combined DCD+TCD method that exhibits the higher sensitivity to defect structures with wide size distributions as compared with any of these methods alone. In the investigated Czochralski-grown silicon crystals, the sizes and concentrations of small oxygen precipitates as well as small and large dislocation loops have been determined using this method.